Wisata Puri: Strategi Memasarkan Bali sebagai Educational Tourism Destination - Sudiarta, I Nyoman Sudiarta; Oka Karini, Ni Made; Juwita Sari, W. Citra (Jurnal Kajian dan Terapan Pariwisata, 2022)
The purpose of this study is to analyze the tourism of the castle from the marketing aspect (potential / product and tourist/market aspects) to build a new concept of Bali as an Educational Tourism Destination. This research was started by conducting a literature study to find out the tourism potential of the castle from various journals, proceedings, and reference books by searching on the google search engine related to "puri tourism", "heritage tourism", "education tourism". Second, a literature study was carried out related to the tourism potential of the world's castles through google search and continued field studies to see firsthand the condition of the castles in Bali. Furthermore, questionnaires were distributed to tourists from Europe and Indonesia to find out their perceptions of castle tourism in Bali. The number of samples of foreign tourists from Europe and America was taken as many as 50 tourists but only 37 tourists were obtained, including domestic tourists, this was due to the Covid 1 pandemic so that only 37 tourists were obtained. Data analysis uses descriptive qualitative analysis that describes the potential and marketing strategies carried out to make Bali an educational tourism destination. The marketing strategy that must be carried out according to the results of this study is an aggressive strategy by marketing through online media and adding something to do activity for tourists and the community